Confidence and competence : developing the mathematical literacy of primary education students in context of a multiliteracies unit - Hamlett, Brenda (Curtin University, 2010)
In order to be effective teachers of mathematics in primary schools, pre-service teachers need to be competent in the relevant curriculum content. In addition, many of them enter university education degree courses with relatively low levels of confidence in mathematics. This research examined the efficacy of a newly developed first year core unit, entitled Becoming Multiliterate, in developing competence and confidence in mathematics amongst students enrolled in BEd degrees in primary and early childhood education who were identified as lacking in one or both areas. Staff members who taught into the unit were conscious of the need to identify shortcomings in a way that did not adversely affect students’ attitudes and confidence and adopted a CRC (Comment, Recommend, Commend) approach during their interactions with students.Students enrolled in the unit completed a diagnostic assessment in the first week and the results of this were used to determine the extent to which concerns about competence were well founded and to enable targeted support to be provided. Students also indicated how confident they felt that they had answered the questions correctly and this data enabled staff to identify and support students whose confidence levels were low or, in some cases, unrealistically high. Students who did not reach the required benchmark then completed a three week mathematics module (one of four comprising the unit) which included tutor assistance, online resources and access to text based and hands on activities. Following this intervention, students had multiple opportunities to sit an exit assessment and any changes in performance were used to determine the efficacy or otherwise of the module materials and approach. Students were also surveyed at the start of the following semester to identify any changes in confidence levels.On entry to the unit student competence and confidence levels were lower than was acceptable for effective teaching of primary mathematics, with some variations between genders and between those enrolled in the primary and early childhood degrees. However, there was no significant variation across age groups despite expectations that mature age students would have lower skill and confidence levels. Particular areas of weakness were noted in the Measurement questions and some aspects of Number.Following the intervention, student performance levels improved significantly and confidence levels were maintained or improved.